Prevalence and antimicrobial resistance of Listeria monocytogenes and Salmonella strains isolated in ready-to-eat foods in Eastern Spain. (January 2015) - Doménech, Eva; Jimenez -Belenguer, Ana; Amoros, Jose Antonio; Ferrus, Maria Antonia; Escriche, Isabel
Abstract: Antimicrobial resistance is a major global public health concern and a food safety issue considered in the framework of Horizon 2020. Bearing this in mind, the current study determined the prevalence of Listeria monocytogenes and Salmonella strains isolated in ready-to-eat food sampled in industry and retail between 2006 and 2012 by the Official Food Control Services of the Valencian administration (Spain). The presence of L. monocytogenes was analysed in a total of 2864 samples including pasteurized cheese (624); cooked ham (487); dried pork sausages (192); ice cream (758) and smoked salmon (803). The presence of Salmonella was analysed in a total of 1264 samples: pasteurized cheese (289); cooked ham (316); dried pork sausages (78); ice cream (376) and smoked salmon (205). The results showed that L. monocytogenes was present in 3.8% of the samples, being most common in smoked salmon. Salmonella was not found in any of the products studied with the exception of 7 out 78 samples of dried pork sausage. Both L. monocytogenes and Salmonella showed resistance to 4 antimicrobials (ampicillin, cephalothin, tetracycline and trimethoprim-sulfamethoxazole). Moreover, the former was resistant to amikacin, ciprofloxacin, erythromycin and vancomycin while the later showed resistance to amoxicillin-clavulanate and chloramphenicol. Furthermore, multi-resistance was found for both microorganisms. Highlights: Prevalence of Listeria monocytogenes and Salmonella strains isolated in ready-to-eat food between 2006 and 2012 was reported. Resistance of positive samples were studied. L. monocytogenes and Salmonella were resistant to ampicillin, cephalothin, tetracycline and trimethoprim-sulfamethoxazole. Multi-resistance was found for both microorganisms in dried pork sausages.